Local matrix-cluster interactions in a phase separated perovskite - Giblin, SR; Terry, I; Prabhakaran, D; Boothroyd, A; Wu, J; Leighton, C (2006)
Magnetoelectronic phase separation plays an integral part in many recent advances in the understanding of correlated electron systems. We have studied the magnetically phase separated material La1-x Srx Co O3 and observe unambiguous evidence of magnetic interactions between hole-rich ferromagnetic clusters and the neighboring hole poor matrix. We suggest that this mechanism detected here plays an important role in the rich electrical and magnetic properties of La1-x Srx Co O3. © 2006 The American Physical Society.